Case Report: Duodenal Carcinoma in a 40-Year-Old Asian Man With Cowden Syndrome - Zhao, Mingkun; Lin, Xiaohan; Fang, Yuan; Zhuang, Aobo; Tong, Hanxing; Lu, Weiqi; Zhou, Yuhong; Zhang, Yong (Frontiers in Surgery, 2022)
Cowden syndrome is a rare autosomal dominant genetic disease mainly shown as systemic multisystem lesions. The incidence of Adenocarcinoma of duodenum with Cowden syndrome in Asian males is rare. A 40-year-old Chinese man was hospitalized because of gastrointestinal hemorrhage and anemia due to infiltrating adenocarcinoma of the descending part of the duodenum. He also had typical signs of Cowden syndrome, such as multiple polyps of the gastrointestinal tract, macrocephaly, papilloma of the tongue, soles hyperkeratosis， and melanosis spots. After the pancreaticoduodenectomy (classic Whipple), the lesions revealed the presence of hamartomatoid polyps, and some of them mutated into nonmucinous adenocarcinoma (80%) and mucinous adenocarcinoma (20%). Further investigation showed a lack of PTEN protein expression in the duodenal neoplasm, and genetic analysis showed the mutation of p.E242fs in PTEN. The patient is followed for one year. There was no appearance of recurrence or distant metastasis.